2014
DOI: 10.1016/j.bbrc.2014.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Role of gamma carboxylated Glu47 in connexin 26 hemichannel regulation by extracellular Ca2+: Insight from a local quantum chemistry study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…It is important to also notice that the interaction of GLU47 and calcium was studied by the means of quantum chemistry methods by Zonta et al [61]. Through their calculations, the researchers explored GLU47, ARG75 and ARG184 with Ca 2+ in a Cx26 hemichannel and their results proved that the post-translational glutamate GLU47 is a strong candidate to bind Ca 2+ in the extracellular side on Cx26.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to also notice that the interaction of GLU47 and calcium was studied by the means of quantum chemistry methods by Zonta et al [61]. Through their calculations, the researchers explored GLU47, ARG75 and ARG184 with Ca 2+ in a Cx26 hemichannel and their results proved that the post-translational glutamate GLU47 is a strong candidate to bind Ca 2+ in the extracellular side on Cx26.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium is a central regulator of keratinocyte differentiation, thus the disruption of calcium hemostasis often results in KID ( Elsholz et al, 2014 ). The p.Gly45 amino acid is located in the first Cx26 extracellular loop (E1) adjacent to p.Glu47 where they are two of the three aminoacids involved in the Ca 2+ binding site for Cx26 gap junction hemichannels ( Bennett et al, 2016 ; Kwon, Tang & Bargiello, 2013 ; Zonta et al, 2014 ). The p.Gly45Glu variant substitutes a negatively charged (acidic) amino acid for a nonpolar one, affecting its localization and interfering with Ca 2+ regulation of hemichannel gating ( Sánchez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The missense variant c.134G>A (p.Gly45Glu) in GJB2 exon 2 is associated with the keratitis-ichthyosis-deafness (KID) syndrome, which is often fatal in the first year of life because of cutaneous infections and septicemia ( Janecke et al, 2005 ). The glycine at position 45 is a highly conserved amino acid across all major connexins ( Zhang & Hao, 2013 ) and its location in the parahelix region (residues 42–50) near the highly conserved Ca 2+ binding amino acids p.Gly45, p.Asp46 and p.Glu47 makes p.Gly45 important in the voltage-dependent loop-gate permeability barrier in Cx26 ( Kwon, Tang & Bargiello, 2013 ; Zonta et al, 2014 ; Bennett et al, 2016 ). Interestingly, in the Japanese population p.Gly45Glu is usually associated with p.Tyr136Stop (c.408C>A) in cis (p.Gly45Glu with p.Tyr136Stop).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemistry computations performed by Zonta et al . had also suggested that Ca 2+ binds to the ɤ-carboxylated E47, altering the local structure of the Cx26 hemichannel and preventing stabilizing interactions with R75 from the same monomer and R184 from an adjacent monomer 71 . These studies differ in the proposed mechanisms of Ca 2+ -dependent block: Bennett et al .…”
Section: Structural Insights Into Channel Gatingmentioning
confidence: 99%
“…suggested that binding of calcium ions generates an electrostatic barrier that inhibits the permeation of cations through the pore 22 ; in contrast, Zonta et al . proposed that extracellular Ca 2+ binding produces structural alterations 71 . It is unclear whether the Ca 2+ electrostatic barrier mechanism (which does not produce steric occlusion of the pore) or the structural alterations (obtained by quantum chemistry computations) could explain loop gating.…”
Section: Structural Insights Into Channel Gatingmentioning
confidence: 99%